2019
DOI: 10.1098/rsta.2018.0045
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical proof: from mathematics to school mathematics

Abstract: Proof plays a central role in developing, establishing and communicating mathematical knowledge. Nevertheless, it is not such a central element in school mathematics. This article discusses some issues involving mathematical proof in school, intending to characterize the understanding of mathematical proof in school, its function and the meaning and relevance attributed to the notion of simple proof. The main conclusions suggest that the idea of addressing mathematical proof at all levels of school is a recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…Lesseig, Hine, & Boardman, (2019) who argue "the centrality of proof of mathematics is indisputable." Some opinions also suggested the importance of mathematical proof (Balacheff, 2010;Basturk, 2010;CadwalladerOlsker, 2011;Rocha, 2019). However, Mukmin & Fa'ani (2020) found the fact that in solving mathematical proof problems, there were still so many misconceptions faced by students that resulted in the low mathematical proof ability of students.…”
Section: Introductionmentioning
confidence: 99%
“…Lesseig, Hine, & Boardman, (2019) who argue "the centrality of proof of mathematics is indisputable." Some opinions also suggested the importance of mathematical proof (Balacheff, 2010;Basturk, 2010;CadwalladerOlsker, 2011;Rocha, 2019). However, Mukmin & Fa'ani (2020) found the fact that in solving mathematical proof problems, there were still so many misconceptions faced by students that resulted in the low mathematical proof ability of students.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, their empirical methodology is suggested as a new and fruitful tool to investigate informal notions such as the simplicity of proof. (iv) School mathematics Helena Rocha characterizes, in Mathematical proof: from mathematics to school mathematics [49], 'the understanding of mathematical proof in school, its function and the meaning and relevance attributed to the notion of simple proof'. It is observed that, in school mathematics, the understanding of proof differs from the understanding in the mathematical research community and, therefore, also the notion of simplicity of proof may be treated differently in school.…”
Section: (Ii) Explanationmentioning
confidence: 99%
“…Above and beyond the role of argumentation as a formal mathematical requirement, in mathematics education it is instrumental in learning [5] and explanation [6], for formulating arguments entails pondering ideas, organizing knowledge, and comparing different points of view [7]. This study consequently focused on argumentation in mathematics education, understood as the mathematical arguments generated by students and teachers in mathematics classrooms [8].…”
Section: Introductionmentioning
confidence: 99%